Have combustible cigarettes met their match? The nicotine delivery profiles and harmful constituent exposures of second-generation and third-generation electronic cigarette users. Issue Volume 26:Issue e1(2017) (11th October 2016) - Wagener, Theodore L; Floyd, Evan L; Stepanov, Irina; Driskill, Leslie M; Frank, Summer G; Meier, Ellen; Leavens, Eleanor L; Tackett, Alayna P; Molina, Neil; Queimado, Lurdes
Abstract : Introduction: Electronic cigarettes' (e-cigarettes) viability as a public health strategy to end smoking will likely be determined by their ability to mimic the pharmacokinetic profile of a cigarette while also exposing users to significantly lower levels of harmful/potentially harmful constituents (HPHCs). The present study examined the nicotine delivery profile of third- (G3) versus second-generation (G2) e-cigarette devices and their users' exposure to nicotine and select HPHCs compared with cigarette smokers. Methods: 30 participants (10 smokers, 9 G2 and 11 G3 users) completed baseline questionnaires and provided exhaled carbon monoxide (eCO), saliva and urine samples. Following a 12-hour nicotine abstinence, G2 and G3 users completed a 2-hour vaping session (ie, 5 min, 10-puff bout followed by ad libitum puffing for 115 min). Blood samples, subjective effects, device characteristics and e-liquid consumption were assessed. Results: Smokers, G2 and G3 users had similar baseline levels of cotinine, but smokers had 4 and 7 times higher levels of eCO (p<0.0001) and total 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanol (i.e., NNAL, p<0.01), respectively, than G2 or G3 users. Compared with G2s, G3 devices delivered significantly higher power to the atomiser, but G3 users vaped e-cigarette liquids with significantly lower nicotine concentrations. During the vaping session, G3 users achieved significantly higher plasma nicotine concentrations than G2 users following the first 10 puffs (17.5 vs 7.3 ng/mL, respectively) and at 25 and 40 min of ad libitum use. G3 users consumed significantly more e-liquid than G2 users. Vaping urges/withdrawal were reduced following 10 puffs, with no significant differences between device groups. Discussion: Under normal use conditions, both G2 and G3 devices deliver cigarette-like amounts of nicotine, but G3 devices matched the amount and speed of nicotine delivery of a conventional cigarette. Compared with cigarettes, G2 and G3 e-cigarettes resulted in significantly lower levels of exposure to a potent lung carcinogen and cardiovascular toxicant. These findings have significant implications for understanding the addiction potential of these devices and their viability/suitability as aids to smoking cessation.